In-line measurement of liquid–liquid phase separation boundaries using a turbidity-sensor-integrated continuous-flow microfluidic device. Issue 12 (22nd April 2022) - Coliaie, Paria; Prajapati, Aditya; Ali, Rabia; Boukerche, Moussa; Korde, Akshay; Kelkar, Manish S.; Nere, Nandkishor K.; Singh, Meenesh R.
Abstract : A novel turbidity-sensor-integrated microfluidic device is developed to quickly measure the liquid–liquid phase separation boundaries. Abstract : Liquid–liquid phase separation (LLPS), also known as oiling-out, is the appearance of the second liquid phase preceding the crystallization. LLPS is an undesirable phenomenon that can occur during the crystallization of active pharmaceutical ingredients (APIs), proteins, and polymers. It is typically avoided during crystallization due to its detrimental impacts on crystalline products due to lowered crystallization rate, the inclusion of impurities, and alteration in particle morphology and size distribution. In situ monitoring of phase separation enables investigating LLPS and identifying the phase separation boundaries. Various process analytical technologies (PATs) have been implemented to determine the LLPS boundaries prior to crystallization to prevent oiling out of compounds. The LLPS measurements using PATs can be time-consuming, expensive, and challenging. Here, we have implemented a fully integrated continuous-flow microfluidic device with a turbidity sensor to quickly and accurately evaluate the LLPS boundaries for a β-alanine, water, and IPA mixture. The turbidity-sensor-integrated continuous-flow microfluidic device is also placed under an optical microscope to visually track and record the appearance and disappearance of oil droplets. Streams of an aqueous solution of β-alanine, pure solvent (water), and pure antisolvent (IPA or ethanol) are pumped into the continuous-flow microfluidic device at various flow rates to obtain the compositions at which the solution becomes turbid. The onset of turbidity is measured using a custom-designed, in-line turbidity sensor. The LLPS boundaries can be estimated using the turbidity-sensor-integrated microfluidic device in less than 30 min, which will significantly improve and enhance the workflow of the pharmaceutical drug (or crystalline material) development process.